Is Fairtrade Fair? - Valiente-Riedl, E. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
Evaluates the capacity of Fairtrade® labeling to enhance the livelihoods of marginalized producers in developing countries. It looks critically at the evolution of fair trade values and markets, including its somewhat controversial engagement with conventional businesses, and problematizes the role of the "ethical consumer.".